THE EFFECT OF ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CLIMATE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AT BRI BANK EMPLOYEES KISARAN BRANCH OFFICE - Regina Dwi Putri Tamara; Nana Dyki Dirbawanto (Transpublika Publisher, 2022)
This study aims to determine and analyze the effect of organizational commitment and organizational climate on organizational citizenship behavior in Bank BRI employees at the Kisaran Branch Office. The sample in this study were all employees of Bank BRI Kisaran Branch Offices as many as 69 respondents. The data analysis method used is validity and reliability test, classical assumption test, multiple regression analysis test, hypothesis test through t-test and f-test, coefficient of determination test. Based on the research, it was found that the variable of organizational commitment has a partial effect on organizational citizenship behavior, this can be proven by the value of tstatistic (4,311) > ttable (1,966). While the organizational climate variable has a partial effect on organizational citizenship behavior, this is evidenced by the value of tstatistic (5,439) > ttable (1,966). Based on simultaneous testing that the variable organizational citizenship behavior simultaneously has a positive and significant effect on organizational commitment and organizational climate tstatistic (59,660) > ttable (3,14) and obtained an R value of 0,802 and the Adjusted R Square in this study is 0,633 then the rest 36,7% is influenced by other variables not discussed in this study.